Hexagonal boron nitride-carbon nanotube hybrid network structure for enhanced thermal, mechanical and electrical properties of polyimide nanocomposites. (1st March 2020) - Park, Ok-Kyung; Owuor, Peter Samora; Jaques, Ygor Morais; Galvao, Douglas Soares; Kim, Nam Hoon; Lee, Joong Hee; Tiwary, Chandra Sekhar; Ajayan, Pulickel M.
Abstract: This study suggests the simple and effective synthesis method of chemically interconnected hexagonal boron nitride (h-BN)–carbon nanotubes (CNTs) hybrid materials (BN–Fe-CNT) with aminosilane functionalized iron oxide nanoparticles (NH2 –Fe) via amide bond formations. Synthesized BN-Fe-CNT was acting as an effective filler that enhanced the mechanical, thermal, and electrical properties of polyimide (PI) nanocomposites and accelerated polycondensation reaction of poly(amic acid) (PAA) due to its high thermal conductivity and heat diffusivity. At a 2 wt% filler reinforcement, the in-plane thermal conductivity of the BN-Fe-CNT/PI reached 15 W m −1  K −1 at 200 °C, which represents an enhancement of approximately 11430% compared to that of pure PI. Moreover, thermal stability was enhanced from 400 °C to 570 °C. Furthermore, the connected CNTs between the individual h-BN produced electron pathways through the PI matrix, with the BN-Fe-CNT/PI exhibiting 10 6 times higher electrical conductivity than that of pure PI. The results in this study clearly suggested that the BN-Fe-CNT could be applicable as an effective multi-functional reinforcement in the fabrication of lightweight polymer nanocomposites with superior mechanical properties, high thermal properties, and high electrical conductivities.